2015
DOI: 10.14687/ijhs.v12i1.3122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of problematic use of mobile phones and quality of sleep among high school students

Abstract: It was aimed to evaluate the problematic use of mobile phones and quality of sleep among high school students. This is a cross-sectional study carried out on 1,131 high school students studying at Sivrihisar, a district of Eskisehir, in December 2012. The questionnaire form include the sociodemographic characteristics, problematic use of mobile phones and quality of sleep. BianchiPhillips problematic use of mobile phones (PUMP) scale and Pittsburgh Sleep Quality Index (PSQI) was used. Median score of PUMP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…The results of other studies among adolescents do not give a clear picture. Two research studies which included a somewhat wider age range compared to our research (11-18 and 13-20 years of age) found that the frequency of problematic use increased with the participants' age (López-Fernández et al, 2014;Öz, Arslantaş, Buğrul, Koyuncu, & Ünsal, 2015), while another study determined that the problematic use increased with age in middle school and the first grade of high school, but then decreased in higher grades of high school, which the authors attributed to greater school responsibilities of older students and preparations for final tests (Louragli, Ahami, Khadmaoui, Mammad, & Lamrani, 2018). By comparing participants 3-11 and 12-19 years of age, Csibi, Griffiths, Demetrovics, and Szabo (2019) found that the younger group of participants was more prone to problematic mobile phone use, but also to various conflicts (being reprimanded by adults for overusing mobile phones), mood swings and lower self-control.…”
Section: Discussioncontrasting
confidence: 46%
“…The results of other studies among adolescents do not give a clear picture. Two research studies which included a somewhat wider age range compared to our research (11-18 and 13-20 years of age) found that the frequency of problematic use increased with the participants' age (López-Fernández et al, 2014;Öz, Arslantaş, Buğrul, Koyuncu, & Ünsal, 2015), while another study determined that the problematic use increased with age in middle school and the first grade of high school, but then decreased in higher grades of high school, which the authors attributed to greater school responsibilities of older students and preparations for final tests (Louragli, Ahami, Khadmaoui, Mammad, & Lamrani, 2018). By comparing participants 3-11 and 12-19 years of age, Csibi, Griffiths, Demetrovics, and Szabo (2019) found that the younger group of participants was more prone to problematic mobile phone use, but also to various conflicts (being reprimanded by adults for overusing mobile phones), mood swings and lower self-control.…”
Section: Discussioncontrasting
confidence: 46%
“…Along with the latest developments in technology, tools like computer, Internet, and cell phones deeply affect people's lives in many areas (Öz, Arslantaş, Buğrul, Koyuncu, & Ünsal, 2015). Internet is a practical resource for getting information and communicating with others and the Internet, seen as one of the most powerful social environments of 21st century, is used by 90% of adolescents for getting information (Eliacik et al, 2016; Gholamian, Shahnazi, & Hassanzadeh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid advancement of technology in the contemporary world, tools like the Internet, social networks such as Facebook, YouTube, Viber, as well as smartphones that have provided the use of the above tools, have profoundly affected people's normal lives [1]. On the one hand, these tools and instruments have caused speed and accuracy in work and expansion of communication, in such a way that the globe has become a global village [2].…”
Section: Introductionmentioning
confidence: 99%